Designating the Implication of Administrative-based learning Supervision on Teacher’s Competency Improvement - Abdul Azis (JIEMAN: Journal of Islamic Educational Management, 2022)
One of the efforts to improve the quality of learning is preparation and careful learning planning. Planning is poured in the form of learning administration as the direction and footing of learning carried out by the teacher. Supervision is an act of quality control of the readiness and completeness of teacher learning administration planning as an inherent task of the principal as a supervisor. The purpose of this study is, first, to test whether the administration of teacher learning is in accordance with the standards set by the school. Second, what are the supporting and inhibiting factors in the preparation and planning of learning administration. This study uses two cycles, each cycle consisting of planning, implementation, and reflection. The research was conducted from August to September with 22 teachers as research subjects. Methods of data collection using observation, interviews, and check list of documents. Data analysis uses percentages based on the criteria reference assessment. The results showed that of the 25 components of supervised learning administration, the first cycle scored 81.50, the second cycle scored 89.45, both cycles were in good category. The results per category are still in the good category even though the acquisition value has increased by 7.95. The analysis of the components showed an increase, namely in the first cycle, most of the components were at a very good level (44%), good (0%), sufficient (16%), and less (40%). Cycle II was very good (44%), good (4%), adequate (48%), and poor (4%). This action research can be said to be successful, although there are obstacles and teacher support in planning learning administration. The obstacles are first, the teacher finds it difficult to carry out classroom action research. Second, the teacher is not proficient in operating excel software. Strong will, adequate school facilities, and support from school management are supporting factors for teachers in planning good learning administration. Salah satu upaya memperbaiki kualitas pembelajaran adalah persiapan dan perencanaan pembelajaran yang matang. Perencanaan dituangkan dalam bentuk administrasi pembelajaran sebagai arah dan pijakan pembelajaran dilakukan guru. Supervisi adalah tindakan quality control kesiapan dan kelengkapan perencanaan administrasi pembelajaran  guru sebagai tugas melekat kepala sekolah sebagai supervisor. Tujuan penelitian ini adalah, pertama, apakah administrasi pembelajaran guru sesuai dengan standar yang ditetapkan sekolah. Kedua, apa faktor pendukung dan penghambat dalam penyiapan dan perencanaan administrasi pembelajaran. Penelitian ini menggunakan dua siklus yang setiap siklusnya terdiri dari perencanaan, pelaksanaan, dan refleksi. Penelitian dilakukan mulai Agustus sampai September dengan subyek penelitian sebanyak 22 guru. Metode pengumpulan data menggunakan observasi, wawancara, dan check list dokumen. Analsis data menggunakan persentase berdasarkan penilaian acuan kriteria. Hasil penelitian menunjukkan bahwa dari 25 komponen administrasi pembelajaran disupervisi, siklus I memperoleh nilai 81,50, siklus II nilai 89,45, kedua siklus kategori baik. Hasil perkategorinya masih kategori baik walaupun meningkat perolehan nilainya 7,95. Analisis perkomponennya menunjukkan peningkatan yakni siklus I sebagian besar komponen berada di level sangat baik (44%), baik (0%), cukup (16%), dan kurang (40%). Siklus II di level sangat baik (44%), baik (4%), cukup (48%), dan kurang (4%). Penelitian tindakan ini dapat dikatakan berhasil, meskipun ada kendala dan penunjang guru dalam merencanakan administrasi pembelajaran. Kendalanya adalah pertama, guru merasa kesulitan dalam melaksanakan penelitian tindakan kelas. Kedua, guru belum mahir dalam mengoperasikan software excel. Kemauan keras, fasilitas sekolah yang memadai, dan dukungan dari manajemen sekolah adalah faktor penunjang guru-guru dalam merencanakan administrasi pembelajaran dengan baik.